Caracterização quali-quantitativa do sistema de abastecimento de água no município de Caicó-RN - Medeiros, Miliane de Souza (Universidade Federal Rural do Semi-Árido, 2018)
Water is a renewable natural resource, fundamental for life and for all human activities, but it is a limited good, where its quality must obey the standards of potability and use, having the power to invigorate health, but it can also cause several problems when contaminated. The objective of this study was to characterize the supply and distribution of water in the municipality of Caicó / RN, identifying the technical operational part and quality of the water at the exit of the treatment, distribution network and sources. Water samples from two sources, one from CAERN and one from 1BEC, were analyzed, verifying the potability and analyzing the efficiency of the CAERN treatment, through physicochemical tests. The samples were collected directly from the sources, and 1L of water was collected from each well. Data were collected from the residents, using a simplified questionnaire, applied to a finite population, with a sample of 170 residences. The water supply of the municipality of Caicó still presents problems in the quantity and quality of water, due to the low level of the source of catchment. Although CAERN is responsible for water supply, it still has a part that is not benefited by the service, generating dissatisfaction with the city's residents due to the lack of quality and quantity of water received. CAERN supplies the city by means of casters of zones, where it was established weekly, 3 days without and 4 with water, where this one does not obey correctly, according to the inhabitants of the city, causing the population to look for alternatives like car-pipes. CAERN's water quality analyzes present results within the potability standards required by ordinance no. 5/ 2017. The water distributed by both the municipal government and the 1ºBEC receive a single treatment, which is the addition of chlorine, the source chosen for the supply had satisfactory physical-chemical analyzes for the raw water parameters.
Monografia
Keywords: Água; Sistema de abastecimento; Caicó; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA